2008
DOI: 10.3732/ajb.0800114
|View full text |Cite
|
Sign up to set email alerts
|

Plant–pollinator interactions in tropical monsoon forests in Southeast Asia

Abstract: Forests with different flora and vegetation types harbor different assemblages of flower visitors, and plant–pollinator interactions vary among forests. In monsoon‐dominated East and Southeast Asia, there is a characteristic gradient in climate along latitude, creating a broad spectrum of forest types with potentially diverse pollinator communities. To detect a geographical pattern of plant–pollinator interactions, we investigated flowering phenology and pollinator assemblages in the least‐studied forest type,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
(41 reference statements)
1
43
0
Order By: Relevance
“…Therefore, the breeding system functional in P. indica is one step evolved in the path of avoiding selfing through autonomous autogamy and the recorded fruit set rate in open-pollinations is a function of vector-mediated self-and cross-pollination. Kato et al (2008) . kerii by Pieridae and R. sootepensis by Hesperiidae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the breeding system functional in P. indica is one step evolved in the path of avoiding selfing through autonomous autogamy and the recorded fruit set rate in open-pollinations is a function of vector-mediated self-and cross-pollination. Kato et al (2008) . kerii by Pieridae and R. sootepensis by Hesperiidae.…”
Section: Discussionmentioning
confidence: 99%
“…Burkhardt (1964) and Faegri & van der Pijl (1979) described that butterflyflowers usually possess large, white, pink, red, yellow or blue, narrow, tubular flowers with deep nectaries and often yellow rings or other markings on the petals which function as nectar guides. Further, Kato et al (2008) stated that the secondary pollen presentation system is often found in butterfly-pollinated species with a long slender corolla-tube and far exserted style. In the present study also, P. indica principally pollinated by butterflies and hawk moths display the characteristics stated by these authors but in this species, nectar guides are totally absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal changes may vary among forest types. In Southeast Asian tropical rain forests, Kato et al (2008) found year-round flower visitors where flowering occurred throughout the year in the presence of supra-annual flowering plants. In this study, the pollen feeders were only abundant in early spring, reflecting their strong habitat and food specificity.…”
Section: Discussionmentioning
confidence: 99%
“…This result was further confirmed by the AMOVA analysis, with 91.57% of the genetic variation existed within populations (Table 4). Afzelia (Caesalpinioideae) species are pollinated by large Xylocopa bee (Kato et al, 2008) to be capable of flying distances of several kilometers thus affecting pollen dispersal between plants at great distances. The gene flow estimates (Nm) was estimated at 3.13, indicating a very high migration rate among 15 populations.…”
Section: Discussionmentioning
confidence: 99%